(untitled) (Prilozi za orijentalnu filologiju, 2021)
The famous Bosniak scholar Ali-dede Bosniak used verious literary, historical and scientific references in his work Muḥāḍara al-ʼawāʼil wa musāmara al- ʼawāḫir (Lectures on the first and last events). In this paper we present the list of such references and its number exceedes fifty units. We have to mention it is not a complete list and does not represent the entire referential framework of this author. A very significant feature of Ali-dede’s intertextual connection with other works is the diversity of areas and topics dealing with the literature to which Ali-dede refers. We have realised that this author refers not only to traditional and well-known Islamic scholars such as al-Suyūṭī and al-Ġazālī, for example, but also to many great Sufi authors, such as ʼIbn ʻArabī and al- Qūnawī, which reflects Ali-dede’s openness to diverse opinions and considerations of both Islam and the history of Islam.